2014
DOI: 10.1016/j.clnme.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

High vitamin B12 levels are not associated with increased mortality risk for ICU patients after adjusting for liver function: A cohort study

Abstract: Background and Aims Recent research has suggested that high vitamin B12 levels may be associated with increased mortality after ICU admission. However, it is known that impaired liver function may lead to elevated B12 since B12 is metabolized through the liver, and therefore high B12 levels may serve as a proxy for poor liver function. The aim of this study is to assess the impact that liver function and liver disease have on the relationship between high vitamin B12 levels and mortality in the ICU. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 28 publications
3
21
1
1
Order By: Relevance
“…Baseline characteristics, such as older age, high blood pressure, reduced eGFR, and elevated UAE rate, as well as increased concentrations of liver enzymes, were positively associated with higher plasma concentrations of vitamin B 12 , in agreement with findings from other studies. 3,8,11 While the cross-sectional associations as found in this study do not provide an insight for a particular cause of death, we observed that high circulating vitamin B 12 plasma concentrations were associated with significantly higher risk of all-cause mortality. The association remained significant after adjustment for established risk factors, including age, sex, BMI, type 2 diabetes, tobacco use, and alcohol consumption, as well as biomarkers associated with renal and liver function.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Baseline characteristics, such as older age, high blood pressure, reduced eGFR, and elevated UAE rate, as well as increased concentrations of liver enzymes, were positively associated with higher plasma concentrations of vitamin B 12 , in agreement with findings from other studies. 3,8,11 While the cross-sectional associations as found in this study do not provide an insight for a particular cause of death, we observed that high circulating vitamin B 12 plasma concentrations were associated with significantly higher risk of all-cause mortality. The association remained significant after adjustment for established risk factors, including age, sex, BMI, type 2 diabetes, tobacco use, and alcohol consumption, as well as biomarkers associated with renal and liver function.…”
Section: Discussioncontrasting
confidence: 75%
“…27 Moreover, we adjusted our results for several confounding variables, including liver function parameters, and found that the association remained, whereas other authors have reported loss of significance after such adjustment. 11 Another strength of this study is the implementation of a robust method of plasma concentration of vitamin B 12 quantification. The accuracy of the assay that we used has been evaluated using the vitamin B 12 World Health Organization International Standard.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 MMA is a functional biomarker for B12 deficiency as it increases in deficiency because cobalamin is required for the cofactors involved in its metabolism. 5 The decrease in serum folate following surgical insult is similar to a previous report 6 but differs from another reporting no change. The hypercobalaminaemia seen in malignancies and inflammatory diseases is therefore not due to acute inflammation as previously speculated 4 and may be related to liver dysfunction rather than inflammation.…”
Section: The Effect Of the Acute Phase Response On Routine Laboratorysupporting
confidence: 83%
“…The hypercobalaminaemia seen in malignancies and inflammatory diseases is therefore not due to acute inflammation as previously speculated 4 and may be related to liver dysfunction rather than inflammation. 5 The decrease in serum folate following surgical insult is similar to a previous report 6 but differs from another reporting no change. 3 The mechanisms for this are unclear.…”
supporting
confidence: 83%